2017
DOI: 10.1063/1.5006934
|View full text |Cite
|
Sign up to set email alerts
|

Similar ultrafast dynamics of several dissimilar Dirac and Weyl semimetals

Abstract: Recent years have seen the rapid discovery of solids whose low-energy electrons have a massless, linear dispersion, such as Weyl, line-node, and Dirac semimetals. The remarkable optical properties predicted in these materials show their versatile potential for optoelectronic uses. However, little is known of their response in the picoseconds after absorbing a photon. Here we measure the ultrafast dynamics of four materials that share non-trivial band structure topology but that differ chemically, structurally,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 62 publications
3
38
0
Order By: Relevance
“…Rapid photo relaxation has been seen in all kinds of different types of Dirac semimetals. 228 The future for applications of TSMs in optical devices thus seems bright.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Rapid photo relaxation has been seen in all kinds of different types of Dirac semimetals. 228 The future for applications of TSMs in optical devices thus seems bright.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Several Shubnikov-de-Haas (SdH) oscillations measurements reported a major peak at ∼240 T, which is attributed to the quasi-2D Fermi surface [16,19,[21][22][23][24][25] while a peak at ∼600 T observed by thermoelectric power [23] and high field SdH [24] measurement is assigned to a 3D Fermi surface. Recently, frequency independent flat optical conductivity [25], the rapid relaxation rate after photoexcitation [26] and Ag tip induced superconductivity [27] are also reported in ZrSiS. Thus, these fascinating phenomena demonstrated that the ZrSiS family is a great system for studying the Dirac nodal-lines [11,12,28,29].…”
Section: Introductionmentioning
confidence: 97%
“…For the magnetic behavior, it displays ferromagnetic (FM) order below T C ∼ 565 K, followed by a transition to canted antiferromagnetic (AFM) order with a net FM component below T F M −AF M ≈ 304 K [3]. The nontrivial topological semimetal behavior was further supported by optical conductivity and ultrafast optical pump-probe measurements [4]. Nevertheless, Ramankutty et al[5] reported zero Berry phase indicative of trivial topology in nearly stoichiometric SrMnSb 2 .…”
mentioning
confidence: 99%
“…4 (f)-(h), these Dirac cones form a line node along the Y-S direction, and two Dirac cones merge at the S point. This is a consequence of two units of MnSb(2) 4 and Sb(1) layers, each of which supports two-dimensional Dirac cones, and the mixing between the two units is suppressed at k x = π.…”
mentioning
confidence: 99%